Pengaruh Electronic Word of Mouth terhadap Keputusan Pembelian Konsumen Komunikoffie - Fasyah, Sandhy Rizqy; Qanti, Sara Ratna; Syamsiyah, Nur; Heryanto, Mahra Arari (Universitas Galuh, 2024)
Komunikoffie is a pioneer industrial garden coffeeshop in Cirebon City that focuses on selling various types of Arabica coffee beans from local agricultural products. However, in the last 3 months (October-December 2023) period, Komunikoffie experienced a 5.3% decline in revenue and a stagnation in the number of customer per month. Electronic Word of Mouth or e-WOM is a consumer statement about a company or product through the Internet, possibly being a major factor in the revenue decline and customer stagnation during that period. This study aims to determine the characteristics and influence of e-WOM on Komunikoffie consumer purchasing decisions. The research employs a survey, quantitative research, and verification design with a sample size of 118 people taken using systematic random sampling. Data analysis techniques include descriptive analysis and multiple linear regression analysis. Based on the research findings, Komunikoffie consumers are predominantly males in the late adolescent age group, 17 to 25 years old, with higher education, students/college students with an average income ranging from Rp.1,000,000.00 to Rp.4,999,999.00, unmarried, and following Komunikoffie's Instagram. Simultaneously, the intensity, positive valence, negative valence, and content variables have a significant influence on consumer purchasing decisions. Partially, the intensity, positive valence, and content variables have a positive and significant impact on Komunikoffie consumer purchasing decisions, while the negative valence variable partially has a negative but not significant effect on Komunikoffie consumer purchasing decisions.